Fatty Acid Synthase and Acetyl-CoA Carboxylase Are Expressed in Nodal Metastatic Melanoma But Not in Benign Intracapsular Nodal Nevi. (April 2018) - Saab, Jad; Santos-Zabala, Maria Laureana; Loda, Massimo; Stack, Edward C.; Hollmann, Travis J.
Abstract : Background: Melanoma is a potentially lethal form of skin cancer for which the current standard therapy is complete surgical removal of the primary tumor followed by sentinel lymph node biopsy when indicated. Histologic identification of metastatic melanoma in a sentinel node has significant prognostic and therapeutic implications, routinely guiding further surgical management with regional lymphadenectomy. While melanocytes in a lymph node can be identified by routine histopathologic and immunohistochemical examination, the distinction between nodal nevus cells and melanoma can be morphologically problematic. Previous studies have shown that malignant melanoma can over-express metabolic genes such as fatty acid synthase (FASN) and acetyl-CoA carboxylase (ACC). This immunohistochemical study aims to compare the utility of FASN and ACC in differentiating sentinel lymph nodes with metastatic melanomas from those with benign nodal nevi in patients with cutaneous melanoma. Materials and Methods: Using antibodies against FASN and ACC, 13 sentinel lymph nodes from 13 patients with metastatic melanoma and 14 lymph nodes harboring benign intracapsular nevi from 14 patients with cutaneous malignant melanoma were examined. A diagnosis of nodal melanoma was based on cytologic atypia and histologic comparison with the primary melanoma. All nodal nevi were intracapsular and not trabecular. Immunohistochemistry for Melan-A, S100, human melanoma black 45 (HMB45), FASN, and ACC were performed. The percentage of melanocytes staining with HMB45, FASN, and ACC was determined and graded in 25% increments; staining intensity was graded as weak, moderate, or strong. Results: All metastatic melanomas tested had at least 25% tumor cell staining for both FASN and ACC. Greater than 75% of the tumor cells stained with FAS in 7/13 cases and for ACC in 5/12 cases. Intensity of staining was variable; strong staining for FASN and ACC was observed in 69% and 50% of metastatic melanoma, respectively. HMB45 was negative in 40% of nodal melanoma cases all of which stained with FASN and ACC. Capsular nevi were uniformly negative for FASN, ACC, and HMB45 immunoreactivity. Conclusions: All metastatic melanoma cases involving sentinel lymph nodes were positive for FASN and ACC while no staining was observed in intracapsular nevi. These findings suggest that FASN and ACC could be used as valuable ancillary stains in the distinction between nodal nevi and metastatic melanoma.